Depression in pregnant women hospitalized due to intrauterine growth restriction: Prevalence and associated factors. (March 2019) - Tsakiridis, Ioannis; Dagklis, Themistoklis; Zerva, Christina; Mamopoulos, Apostolos; Athanasiadis, Apostolos; Papazisis, Georgios
Abstract: Objective: Pregnancies complicated with intrauterine growth restriction (IUGR) may require hospitalization in a high-risk pregnancy unit (HRPU). A complicated pregnancy and hospital admission may negatively affect the pregnant woman's mental health. Several factors have been identified as possible risk factors for depression, which is proven to lead to several adverse perinatal outcomes. The purpose of this study was to screen for depression in women admitted to an HRPU due to IUGR pregnancy and also to identify associated risk factors. Study design: All pregnant women admitted at ≥ 24 gestational weeks with the diagnosis of IUGR were eligible for the study. The Greek version of the Edinburgh Postnatal Depression Scale was used as screening tool on admission. A cut-off score ≥ 13 was used to identify depression, while possible risk factors were also investigated. Results: Overall, 73 women were eligible for the study and agreed to complete the questionnaire. The mean age of the pregnant women was 31.4 ± 6.7 years and the mean gestational week at admission was 33.6 ± 2.9 weeks. The prevalence of depressive symptoms (score ≥ 13) was 32.9% (24/73). In the multivariable model, depressive symptoms were significantly correlated with lower gestational age (OR: 3.459 95%CI: 1.124–10.648) and smoking during pregnancy (OR: 3.926 95% CI: 1.141–13.507). Conclusions: About one third of pregnant women hospitalized in the HRPU with IUGR pregnancies showed signs of depression at the time of admission. Early-IUGR and smoking were found to be associated with antenatal depressive symptoms.